Analytical Study of Homogenization Causes in Translating Verbal Similar (Mutashābih) Verses into Persian, Case Study: Rezaei Esfahani’s Translation - Ensiyeh Sadat Hashemi (دراسات فی اللغه العربیه و آدابها)
In an ST-oriented translation, the translator tries to avoid changes. One of the translation changes is the homogenization that Antoine Berman refers to in his analytical model, which is the unification of the textural diversity of the origin. One of the translations that is most careful in preserving the differences of similar verbal verses is Rezaei Esfahani's translation. Comparative studies in this field have indicated that this translation is more successful than other translations in this field. The present article, with a descriptive-analytical approach, examines the translation of similar verbal verses in terms of preserving subtle differences between them and studies the homogenization causes in the translation of these verses. The conclusion of this study is that the main reason of homogenization in translating similar verbal verses is the structural differences between Arabic and Persian. Some of these reasons are: the conformity of the adjective with the noun, derivation, transitive verb by the preposition, relative pronoun, the reduction and the gender. The variety of synonyms and letters in Arabic are the other factors of homogenization in Persian translation. This research shows that Rezaei Esfahani has consciously homogenized in cases where a phrase in one verse has been mentioned and, in another verse, has been omitted, and the translator has mentioned the deleted phrase in parentheses, according to the other verse.